2018
DOI: 10.1111/cas.13572
|View full text |Cite
|
Sign up to set email alerts
|

c‐Src inhibitor selectively inhibits triple‐negative breast cancer overexpressed Vimentin in vitro and in vivo

Abstract: Oncogene c‐Src has been found to be a potential target for the treatment of triple‐negative breast cancer (TNBC). However, the therapeutic effects of the c‐Src inhibitor on TNBC patients are controversial compared to those on cell lines. The molecular mechanisms of the inhibitory effects of the c‐Src inhibitor on TNBC remain unclear. Herein, we showed that a specific c‐Src inhibitor, PP2, was effective in inhibiting phosphorylation of c‐Src in 4 cell lines: T‐47D, SK‐BR‐3, SUM1315MO2, and MDA‐MB‐231, regardles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 45 publications
(107 reference statements)
1
13
0
Order By: Relevance
“…Src inhibitor PP2 reduced the S phase of cell cycles and inhibited colony formation, blocked cell migration/invasion and EMT in triple-negative breast cancer cell lines. Vimentin expression in this study was suggested as a potential biomarker to identify responsive cancer cell populations associated with an EMT phenotype [65]. The mesenchymal transition in breast cancer could be stimulated by different mechanisms, and it has been widely cited as an effective event associated with the promotion ability of Src in breast cancer.…”
Section: Breast Cancermentioning
confidence: 87%
“…Src inhibitor PP2 reduced the S phase of cell cycles and inhibited colony formation, blocked cell migration/invasion and EMT in triple-negative breast cancer cell lines. Vimentin expression in this study was suggested as a potential biomarker to identify responsive cancer cell populations associated with an EMT phenotype [65]. The mesenchymal transition in breast cancer could be stimulated by different mechanisms, and it has been widely cited as an effective event associated with the promotion ability of Src in breast cancer.…”
Section: Breast Cancermentioning
confidence: 87%
“…The high expression of Estrogen Receptor (ERα) and HER2 were firstly reported as favorable indicators for the use of c-Src inhibitors in breast cancer cell lines [ 75 , 76 ]. Recently, it has been reported that triple negative breast cancer (TNBC) cells also showed sensitivity to c-Src inhibitors [ 79 ]. Lou and colleagues reported that c-Src inhibitors were able to prevent TNBC invasive ability by determining a significant decrease in vimentin expression.…”
Section: Current Status Of C-src Inhibitors and Their Effects In Dmentioning
confidence: 99%
“…Lou and colleagues reported that c-Src inhibitors were able to prevent TNBC invasive ability by determining a significant decrease in vimentin expression. Thus, authors suggested vimentin as a predictive biomarker to stratify breast cancer patients in clinical trials testing c-Src inhibitors [ 79 ].…”
Section: Current Status Of C-src Inhibitors and Their Effects In Dmentioning
confidence: 99%
“…Although some studies have shown that vimentin expression is a marker for poor prognosis [36], others have reported that its high expression can sensitize triple-negative breast cancer in vitro and in vivo to the c-Src inhibitor (dasatinib) [37,38]. Moreover, depletion of vimentin mitigates the c-Src inhibitory effects, suggesting that vimentin plays a role in the regulation of c-Src [38,39]. In line with our findings showing that LQB-223 reduced cell migration, treatment with LQB-223 reduced mRNA levels of KRT18 and increased CLDN3 .…”
Section: Discussionmentioning
confidence: 99%